Estimación de la evapotranspiración para la gestión del riego de los cultivos de caucho natural en el municipio de Puerto López, departamento del Meta; a partir de estaciones meteorológicas e imágenes MODIS (2023)
This work estimates and analyzes the evapotranspiration behavior of natural rubber crops in plantations in the municipality of Puerto López, Meta; in order to evaluate the irrigation management (important to preserve the water resource) that is carried out on these crops; because they are crops that occupy a good part of the national territory, that have a quite long productive stage (with good agricultural practices) and that, at some point in Colombian history, new areas of expansion of these crops were contemplated; however, little is said about this species.